Guidance for Rehabilitation Patients with COVID-19 Discharged from Hospital with Integration of Traditional Chinese and Western Medicine - Jing ZHOU; Yangpu ZHANG; Yujun LUO; Ziying CHEN; Qin LUO; Yan ZHAO; XIAWenguang (康复学报)
The current epidemic prevention and control of COVID-19 has achieved periodical success. Large number of patients with COVID-19 recovered and discharged from the hospital. Most of them still have the clinical problems in respiratory function, physical function, psychological function, daily living ability and social participation ability obstacles. We have developed a set of rehabilitation guidance of integrated Chinese and Western medicine after clinical application. Before the treatment, the patients need a comprehensive rehabilitation assessment, including respiratory function, cardiopulmonary function, physical function, psychological function and the ability of daily activities. From the perspective of TCM rehabilitation, we have designed a set of TCM rehabilitation technical scheme including Tuina, traditional exercise, Chinese herbs, moxibustion, foot bath, TCM diet. At the same time, this guidance is also combined with respiratory function training, airway clearance techniques, physical function training. In addition, to solve the psychological problems caused by a long-term isolation treatment, we use the traditional music therapy and empathy therapy which are easy for patients to accept. The whole set of guidance integrates the rehabilitation techniques commonly used in Chinese and Western medicine, which is easy to learn and use. We hope that patients can take appropriate rehabilitation methods under the guidance of professionals after discharge from the hospital to accelerate the rehabilitation process and return to society as soon as possible.